2012
DOI: 10.1016/j.semnephrol.2012.07.002
|View full text |Cite
|
Sign up to set email alerts
|

High Risk of ESRD in Type 1 Diabetes: New Strategies Are Needed to Retard Progressive Renal Function Decline

Abstract: Care of patients with Type 1 diabetes (T1D) has changed during the last 30 years. Tools to control glycemia have improved and it was demonstrated that improvement in glycemic control diminished the risk of late diabetic complications, including nephropathy. Moreover, in patients with impaired renal function, aggressive treatment of hypertension and reno-protective blockade of the renin-angiotensin system were shown to postpone end-stage renal disease (ESRD), albeit for a short while. Despite these achievements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 52 publications
3
24
0
Order By: Relevance
“…Unfortunately, the ONTARGET and ALTITUDE studies have further highlighted the limitations of RAAS inhibition, since combination therapies with multiple RAAS blockers increase the risk of serious adverse events 29, 30 . Therefore, a large residual DN risk remains despite current evidence-based intervention strategies and novel therapies to safely complement glucose and RAAS inhibition are urgently needed 3, 26 .…”
Section: Limitations Of Current Approaches To Prevent Esrd In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the ONTARGET and ALTITUDE studies have further highlighted the limitations of RAAS inhibition, since combination therapies with multiple RAAS blockers increase the risk of serious adverse events 29, 30 . Therefore, a large residual DN risk remains despite current evidence-based intervention strategies and novel therapies to safely complement glucose and RAAS inhibition are urgently needed 3, 26 .…”
Section: Limitations Of Current Approaches To Prevent Esrd In Diabetesmentioning
confidence: 99%
“…While such improvements in clinical care have been effective at delaying the development of diabetic complications 1 , the overall incidence of end-stage renal disease (ESRD) due to diabetes has not declined 2, 3 and diabetic nephropathy (DN) remains a major cause of morbidity and mortality among diabetic patients 46 . Thus, novel strategies are urgently needed to complement the existing ones in order to prevent kidney function loss in diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…New effective therapies are desperately needed to reduce risk of ESRD in T1D as it was discussed in the recent issue of Seminars in Nephrology [53]. In designing therapies for T1D it is important to put aside the previous proteinuria-centric model of diabetic nephropathy and fully appreciate the features of progressive renal decline.…”
Section: Progressive Renal Decline and Considerations For Therapeuticmentioning
confidence: 99%
“…12 Studies demonstrated that early hyperglycemia stimulates the production of ECM components, mainly fibronectin and collagen IV, and this effect appears to be mediated by transforming growth factor beta 1 (TGF-b1) in streptozotocin (STZ)-induced diabetic rats, 13,14 as well as, in other models of renal injury. 15,16 Currently, no specific therapy is available to inhibit the progression of renal diabetic disease, and although some studies have demonstrated the renoprotective action of pharmacological therapies that target the glycemic and blood pressure controls, 17,18 the incidence of diabetic nephropathy continues to increase. 1 Regular exercise training is considered an unquestionable component of a healthy lifestyle and widely accepted in the management and prevention of several chronic diseases.…”
Section: Introductionmentioning
confidence: 99%